KARAKTERISTIK BATUAN METAMORF BAYAH di DESA CIGABER, KABUPATEN LEBAK, PROVINSI BANTEN - Patonah, Aton; Syafri, Ildrem (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
Metamorphic rocks in Bayah Complex included by Bayah mountain zone. Purpose of this research is to know characteristic of this rock with using petrography methods, that is, identify texture, structure, mineral contain, and metamorphic facies of the rocks. The result showed that kind of the rock is dominated by biotite schist, some actinolite schist, hornblend schist and chlorite schist. Almost all them have retrograde metamorphism, is characterized by biotite altered to chlorite and muscovite, hornblende to actinolite, and actinolite to chlorite. This proses probably associated by uplift processes in Eocene – Oligocene.